Teacher Readiness in Teaching and Learning History Process through i-Think Mind Maps - Mazlan Husin; Mohd Mahzan Awang; Anuar Ahmad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2017)
This research is aimed at investigating the readiness of History subject teachers in teaching and learning with the help of i-Think mind maps at secondary schools in the district of Setiu, Terengganu. The amount of sample chosen is 59 History teachers from secondary schools which consists of trained teachers without taking into account their specialization. As a whole, the research findings show that respondents have a high readiness level in implementing their teaching and learning process with the help of i-Think mind maps in secondary schools. The findings also show that there is a difference in teacher readiness between history teacher and non-history teacher and between those that went to courses and those who did not. Furthermore, there is a difference in the attitude, skill and usage level of i-Think mind maps in teachers that are experienced and those less experienced. However, research findings for experienced and less-experienced teachers showed that there are no significant differences in the level of knowledge on the concept of i-Think mind maps.